Means of Expressing Locativity in Press News and Reports - Spasić, Jelena Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
This paper analyses the most frequent linguistic means of expressing locativity in news and reports in daily print media. The analysis has been conducted on concrete linguistic excerpts from Serbian newspapers published throughout Serbia. The aim of the paper is to show characteristics of expressing locativity in contemporary Serbian newspapers. Furthermore, the paper also aims to determine the differences between the two journalistic formats (news and reports) by the choice of spatial expressions with static meaning. The research is a contribution to journalism stylistics, more precisely to the Serbian language newspaper stylistics, it also contributes to the study of linguistic and stylistic characteristics of non-literary texts. The most frequent linguistic means of locativity in news and reports are expressions with toponyms, adverbs, and adverbial phrases.
Keywords: stylistics; journalism stylistics; news; news report; locativity